Superficially Similar Adaptation Within One Species Exhibits Similar Morphological Specialization but Different Physiological Regulations and Origins - Zhang, Yi; Wang, Xing-Xing; Feng, Zhu-Jun; Cong, Hao-Su; Chen, Zhan-Sheng; Li, Yu-Dan; Yang, Wen-Meng; Zhang, Song-Qi; Shen, Ling-Feng; Tian, Hong-Gang; Feng, Yi; Liu, Tong-Xian (Frontiers in Cell and Developmental Biology, 2020)
Animals have developed numerous strategies to contend with environmental pressures. We observed that the same adaptation strategy may be used repeatedly by one species in response to a certain environmental challenge. The ladybird Harmonia axyridis displays thermal phenotypic plasticity at different developmental stages. It is unknown whether these superficially similar temperature-induced specializations share similar physiological mechanisms. We performed various experiments to clarify the differences and similarities between these processes. We examined changes in the numbers and sizes of melanic spots in pupae and adults, and confirmed similar patterns for both. The dopamine pathway controls pigmentation levels at both developmental stages of H. axyridis. However, the aspartate-β-alanine pathway controls spot size and number only in the pupae. An upstream regulation analysis revealed the roles of Hox genes and elytral veins in pupal and adult spot formation. Both the pupae and the adults exhibited similar morphological responses to temperatures. However, they occurred in different body parts and were regulated by different pathways. These phenotypic adaptations are indicative of an effective thermoregulatory system in H. axyridis and explains how insects contend with certain environmental pressure based on various control mechanisms.